Diagnosis of Indian Big Four and monocled Cobra snakebites in envenomed plasma using smartphone-based digital imaging colourimetry method. - Upasana Puzari; Mojibur R Khan; Ashis K Mukherjee (PLoS Neglected Tropical Diseases)
Background Venomous or dry bites can result from snake envenomation. Therefore, developing a detection test for venomous snakebites in envenomed patients can prevent from unnecessary antivenom therapy for dry bites, thereby, saving them from adverse effects and cost of antivenom therapy. Methodology This study demonstrates a method for the diagnosis of medically significant 'Big Four' Indian snake venoms (Naja naja, Bungarus caeruleus, Daboia russelii, Echis carinatus) in the plasma of experimentally envenomed animals (envenomed under laboratory conditions). Rabbit polyclonal antibodies (PAbs) were produced by generating modified bespoke peptides identified by computational analysis from the antigenic sites of the main toxins found in the proteome of India's 'Big Four' venomous snakes. The polyclonal antibody formulation (FPAb) prepared by mixing the five representative PAbs in the ratio of 1:1:1:1:1 demonstrated synergistic immune recognition of the 'Big Four' snakes and Naja kaouthia venoms. The recognition for these venoms under in vitro and in vivo conditions by FPAb was significantly higher (p<0.05) than commercial polyvalent antivenom produced against native venom toxins. The FPAb was tested to detect the venoms in subcutaneously envenomed rat plasmas until 240 minutes post-injection. Fourier-transform infrared spectroscopy, zeta potential, transmission electron microscopy, and atomic force microscopy characterised gold nanoparticles (AuNP) conjugated with FPAb. The FPAb-conjugated AuNP demonstrated aggregation upon interaction with venom toxins, changing the colour from red through burgundy to blue, monitored using a smartphone. From the digital image colourimetry analysis of the images, calibration curves for venoms were obtained, and each venom in the envenomed plasma at different time intervals was quantified using these curves. Conclusion A method for detection of venomous snakebites has been reported. The formulation of polyclonal antibodies generated against toxins of 'Big Four' venomous snakes of India immune-recognise venoms of 'Big Four' venomous snakes of India and N. kaouthia venoms under both in vitro and in vivo conditions. The antibody formulation conjugated to AuNP detected the venoms in envenomed plasma. This method of detection has potential to be useful for snakebite management in clinical settings.